Design of terahertz CMOS integrated circuits for high-speed wireless communication - Fujishima, Minoru (Materials, circuits and devices series ;, 2019)
The book comprises of 5 chapters and covers most of our current knowledge, from the background to the design of a terahertz complementary metal oxide semiconductor (CMOS) transceiver for realizing ultrahigh-speed wireless communication.